Influence of drip irrigation and polyethylene mulch on growth, yield and water productivity of tomato (Solanum lycopersicum) and brinjal (Solanum melongena) cultivars in eastern plains - SHIVANI, SHIVANI; BHUTIA, T L; KUMAR, SANJEEV; SINGH, A K (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was carried out during 2014-15, 2015-16 and 2016-17 in silty clay loam soil of Bihar, to study the effect of drip irrigation and black polyethylene mulch compared with furrow irrigation on growth, yield and water productivity of tomato (Solanum lycopersicum L.) and brinjal (Solanum melongena L.). Drip irrigation influenced the growth and yield characters of both vegetable crop as compared to furrow method of irrigation. Further, drip irrigation significantly increased the fruit yield of tomato and brinjal by 26.9 and 40 percent, respectively. Mulching also had a positive effect on yield attributing characters, viz. days taken to flowering, average single fruit weight and number of fruits/plant of both tomato and brinjal. Use of black polyethylene mulch gave 38.6 and 44.6% higher yield of tomato and brinjal compared with unmulched treatments (35 and 26 t/ha, respectively).Tomato variety Swarna Sampada and brinjal variety Swarna Shobha performed better over other varieties irrespective of drip and mulch. Drip irrigation in combination with black polyethylene mulch significantly increased the plant height, dry matter production, number of fruits/plant, fruit weight and finally raised the tomato yield and brinjal yield to 54.4 and 44.45 t/ha with 34% water saving. The average water productivity (17.0 and 13.9 kg/m3) of tomato and brinjal was also maximum in drip irrigated mulched crops.